Challenging human creativity: an exercise of co-creation with generative artificial intelligence - Flores Heymann, Bernardo; Briedis, Mindaugas (Creativity Studies, 2025)
This paper explores the collaborative potential between humans and generative artificial intelligence in creative contexts through a co-creation framework. The study uses ChatGPT to develop narrative elements such as slogans, taglines, and claims for university marketing programs, comparing human-generated and artificial intelligence-generated content to evaluate effectiveness and engagement. Results indicate that while artificial intelligence can contribute useful and creative content, human participants still prefer human-generated narratives in many instances. The study also highlights how generative artificial intelligence can enhance creative processes by accelerating ideation and reducing cognitive load, but it raises concerns regarding the originality and diversity of artificial intelligence-generated content. This research provides insights into the integration of artificial intelligence in collaborative creative work and suggests best practices for leveraging artificial intelligence tools in marketing and communication strategies.